ISLAMIC WEALTH MANAGEMENT DURING THE COVID-19 PANDEMIC - Utari Evy Cahyani; Rizal Ma'ruf Amidy Siregar; Rodame Monitorir Napitupulu (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2021)
The coronavirus disease (COVID-19) pandemic has severe health effects and serious implications for economic. This research is a conceptual article that describes concepts and principles of Islamic wealth management (IWM), Islamic financial planning practice during Covid-19 pandemic, and Islamic social finance for reducing the pandemic effect. There are five stages in IWM that is wealth accumulation, wealth consumption, wealth purification, wealth distribution, and wealth protection. Wealth distribution such as alms, grant, and waqf are important in reducing social and economic impacts due to a pandemic. The existence of Islamic social financial institutions becomes very important to manage that fund. In other hand, practicing Islamic financial planning in household level can mitigate potential poverty in the crisis period. The financial planning manage the provision given by Allah as well which is beneficial for the life of the world and for the afterlife.